Pengembangan Aplikasi Web Mobile Penjadwalan Tugas Aparatur Desa Untuk Meningkatkan Layanan Masyarakat - Rudi Aprianto; Wulandari Wulandari; Nurul Hafifah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
Each Village Device has different tasks and responsibilities and sometimes also has a sudden task, so it takes a task scheduling so that all work can be organized and completed on time. Because of this, the researcher makes an app scheduling the task of mobile village based web apparatus. This application uses the development method of System Development Life Cycle, PHP and MySql programming languages as database. The results of this study indicate that the application of mobile web-based village apparatus scheduling can be applied to help simplify the work of the village apparatus especially in the time discipline so as to create effective and efficient to improve the service to the community.